Local and Systemic Complications after Intravitreal Administration of Anti-Vascular Endothelial Growth Factor Agents in the Treatment of Different Ocular Diseases: A Five-Year Retrospective Study. (March 2015) - Nuzzi, Raffaele; Tridico, Federico
Abstract Purpose: To observe the frequency of complications in patients undergoing intravitreal anti-VEGF injections for different ocular diseases in a five-year period. Materials and Methods: Charts of patients receiving intravitreal anti-VEGF were retrospectively reviewed. Out of 1173 eyes, 762 were treated with bevacizumab, 382 with ranibizumab, and 29 with pegaptanib. Data recorded included demographic information, clinical findings, total injections received, and info about the onset of adverse effects. Results: 12.86% of the eyes treated with bevacizumab presented side-effects, while ratings in the ranibizumab and pegaptanib groups were 15.97% and 20.69%, respectively. Odds ratios calculated comparing incidences after each anti-VEGF are 0.78 (bevacizumab versus ranibizumab, p = 0.152), 0.57 (bevacizumab versus pegaptanib, p = 0.227), and 0.73 (ranibizumab versus pegaptanib, p = 0.508). A total of 185 complications were detected (62.16% after bevacizumab). Ocular side-effects registered were 40 cases of sustained intraocular pression (IOP) elevation, one infectious uveitis, one retinal detachment, and one sub-retinal hemorrhage. Other cases were related to transient IOP elevation immediately after injection. Systemic complications registered were one case of nausea, one episode of chest pain with acute vision loss, and one case of acute blood hypertension. Conclusions: The majority of significant complications occurred in patients receiving multiple bevacizumab administrations. However, results may be affected by the difference in the utilization amount for each drug. AMD patients were the most represented, probably due to greater indication to treatment.